Relevance of Race and Ethnicity for Self-Reported Functional Limitation - Spencer, S. Melinda (2008)
It is unclear whether older adults of different race or ethnicity vary in the ways they perceive functional limitations. Variation in such self-reports may be relevant clinically, because many diagnoses (and subsequent care) depend on self-reported disability. To examine this question, self-reported hand function was compared with performance-based assessment of strength (hand dynamometer) and dexterity (Moberg Pick-Up Test) in white (n = 102), African-American (n = 67), and Hispanic (n = 196) elderly people. Participants were Medicare beneficiaries from northern Manhattan, New York City, aged 70 and older. In adjusted analyses, self-reported hand function was associated with weaker grip strength in African-American and Hispanic participants but not in white participants. Self-reported difficulty with hand function was associated with poorer dexterity in all three groups. Similar results were observed in the subsample of participants with arthritis. These results suggest that culture or socioenvironmental differences associated with culture may influence reports of functional limitation.